2005
DOI: 10.1007/s00198-005-1846-z
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis case finding in the general practice: phalangeal radiographic absorptiometry with and without risk factors for osteoporosis to select postmenopausal women eligible for lumbar spine and hip densitometry

Abstract: Mass screening for osteoporosis using DXA measurements at the spine and hip is presently not recommended by health authorities. Instead, risk factor questionnaires and peripheral bone measurements may facilitate the selection of women eligible for axial bone densitometry. The aim of this study was to validate a case finding strategy for postmenopausal women who would benefit most from subsequent DXA measurement by using phalangeal radiographic absorptiometry (RA) alone or in combination with risk factors in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Finally, this study did not assess the cost-effectiveness of scenarios involving a pre-selection of sub-populations at high risk of osteoporosis. Earlier studies have shown that selective case-finding based on a combination of risk factors, with or without radiographic absorptiometry, provided a better sensitivity and specificity in identifying women with underlying osteoporosis than the currently accepted criteria for reimbursement of DXA measurements in Switzerland [59]. In addition, the pre-selection of women and men at highest risk of osteoporosis, and who should therefore undergo BMD measurement by DXA, based on the determination of their 10-year absolute fracture risk may considerably improve the cost-effectiveness of the population-based screen-and-treat approach [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study did not assess the cost-effectiveness of scenarios involving a pre-selection of sub-populations at high risk of osteoporosis. Earlier studies have shown that selective case-finding based on a combination of risk factors, with or without radiographic absorptiometry, provided a better sensitivity and specificity in identifying women with underlying osteoporosis than the currently accepted criteria for reimbursement of DXA measurements in Switzerland [59]. In addition, the pre-selection of women and men at highest risk of osteoporosis, and who should therefore undergo BMD measurement by DXA, based on the determination of their 10-year absolute fracture risk may considerably improve the cost-effectiveness of the population-based screen-and-treat approach [60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that peripheral low BMD identified women with osteoporosis defined by axial DXA [28,29]. Moreover, Miller et al have reported that low peripheral BMD, regardless of sites measured, was associated with twofold or more increased risk of subsequent fractures [14].…”
Section: Discussionmentioning
confidence: 99%
“…The following papers in our review indicated sponsorship or conflicts of interest, as noted • Bovier et al: 13 The 51 Support by the Health Authority of the Canton of Geneva • Gasser et al: 38 Provision of the digital processing system: Merck Sharp and Dohme-Chibret AG Switzerland • Gauthey et al: 14 Grant from the President of the State Department for Health and Social Affairs • Gugelmann et al: 15 Financial support of the study by SmithKline Beecham corporation • Hayoz et al: 27 Support by a grant from Bristol-Myers Squibb and Sanofi-Synthelabo • Jimmy and Martin: 53 Financial support by Helsana AG • Marki et al: 55,56 Financial support of the study by Health Promotion Switzerland (project 1191)…”
Section: Sponsorship/conflicts Of Interestmentioning
confidence: 95%
“…Twelve studies addressed the prevention of infectious diseases, especially influenza by providing vaccinations [11][12][13][14][15][16][17][18][19][20][21][22] or by performing a specific diagnostic test. 22 For clinical topics, most prevention activities addressed cardiovascular disease prevention, [23][24][25][26][27][28][29][30] cancer screening, [31][32][33][34] HIV, [35][36][37] prevention of osteoporosis, 38,39 addiction prevention, 40,41 and others [42][43][44][45][46][47] (Table 2). The most common observed intervention was counseling on lifestyle changes with twelve studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation